The protective role of steroids on coronary arteries in the acute phase of Kawasaki disease for high risk patients: a retrospective study - Marchesi, Alessandra; Recupero, Rosanna; Sardella, Letizia; Babini, Riccardo; Gargiullo, Livia; Tarissi de Jacobis, Isabella; Cotugno, Nicola; Bozzola, Elena; Marchili, Maria Rosaria; De Benedetti, Fabrizio; Villani, Alberto (Frontiers in Pediatrics, 2025)
PurposeThe incidence of coronary artery aneurysms in Kawasaki disease has been increasing for reasons that remain unclear. Recently the use of corticosteroids in KD has been reconsidered for high-risk patients. To evaluate their effectiveness as first line therapy in combination with IVIG and aspirin for selected KD patients, we performed this retrospective single-center study.MethodsWe retrospectively analyzed KD patients (aged 30 days to 18 years) who were hospitalized at the Bambino Gesù Children's Hospital between December 2007 and February 2023. The patients were classified as “high risk (HR)” or “low risk (LR)” for IVIG resistance and/or developing CAA according to the Italian guidelines and were stratified by treatment. We also analyzed changes in AHA risk class in the HR-S and HR-NS groups. Furthermore, to obtain a single representative Z-score for each patient, we introduced a novel calculation method: a. Z-MAX: the maximum value of the scores between the three coronary arteries. b. Z-SUM: the sum of the single Z-scores of the three coronary arteries.Results374 patients were enrolled, 78 with CAA and 296 without CAA. Of those, 195 patients were classified as HR and all subsequent analyses in this study were exclusively conducted on this subgroup. At the end of the eight weeks, the HR-S group showed a significant reduction in coronary artery dimensions expressed as Z-score (reduction of 65% in RCA, 63% in LMCA, and 36.5% in LAD). In contrast, the HR- NS group showed an increase in the dimension of two arteries (RCA increased by 17% and LAD increased by 15%) and a slight reduction of LMCA (7.5%).ConclusionFirst-line therapy with IVIG plus steroids in HR-KD patients reduces the development of CAA.